Estimation of genetic variation at the DNA level from restriction endonuclease data. - Ewens, W J (1981)
We consider the estimation of the genetic variation in a natural population when the data are obtained by the use of restriction endonucleases. Under the restriction endonuclease technique, a particular DNA segment is considered and cut wherever a recognition sequence appropriate to the endonuclease occurs. We consider data generated when a random sample of homologous DNA segments is treated in this way with one or a battery of restriction endonucleases. The numbers and sizes of the fragments that result indicate the locations and the frequencies of the recognition sequence (or, with a battery of restriction endonucleases, of each recognition sequence). These frequencies in the sample form the basis for an estimate of the amount of genetic variation in the population.